DAYA TERIMA MAKANAN PADA PASIEN DIABETES MELITUS TIPE 2 DENGAN KOMPLIKASI DI RUANG PERAWATAN INTERNAL RS MARDI WALUYO LAMPUNG - Mangalik, Gelora; Sanubari, Theresia Pratiwi Elingsetyo; Maharani, Claudia Cipta (Care : Jurnal Ilmiah Ilmu Kesehatan, 2020)
Food Acceptance is a person's ability to spend food that is served following their needs. Low acceptance of food can increase the risk of malnutrition and affect the nutritional status and healing of patients. This study aims to identify the acceptability of food for patients with type 2 Diabetes Mellitus with complications in the internal care room at Mardi Waluyo Hospital in Lampung. The method used is descriptive quantitative with the cross-sectional design carried out to 53 respondents with a purposive sampling technique of sample collection. The study was conducted in March-April 2019. The results showed that research on respondents in this study showed that respondents mostly depend on the age range of 40-65 years by 65%, 72% of women, have a risk of disease ≥ 2 of 68 %, and respondents who fall into the category of overweight and obesity by 47%. Based on the average distribution of the rest of the respondent's food by 77.4%, based on the attributes of food according to the good category with a value of ≥ 80%. This study concludes that resources about leftovers in patients with type 2 diabetes with complications are not good with leftovers ≥ 25%. Based on food attributes according to the good category.